2014
DOI: 10.1074/jbc.m114.556365
|View full text |Cite
|
Sign up to set email alerts
|

RNA Granule Assembly and Disassembly Modulated by Nuclear Factor Associated with Double-stranded RNA 2 and Nuclear Factor 45

Abstract: Background: RNA granules are associated with translational control and neurodegenerative disease. Results: Nuclear factor associated with dsRNA 2 (NFAR2) enhances RNA granule assembly through two domains, one of which is antagonized by nuclear factor 45 (NF45). Conclusion: NFAR2 and NF45 play novel regulatory roles in RNA granule assembly and disassembly. Significance: Mechanisms of RNA granule assembly and disassembly are the basis for understanding translational control and neurodegenerative disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 62 publications
3
26
0
Order By: Relevance
“…As expected, the poly(I:C)-stimulation-caused circRNA reduction could be noticeably rescued by overexpression of NF90 for examined circRNAs ( Figure 4I). Furthermore, it has been shown that the NF90/NF110 export depends on PKR activation and phosphorylation upon infection (Harashima et al, 2010;Shiina and Nakayama, 2014). Consistent with these studies, we found that NF90/NF110 were no longer exported to the cytoplasm upon poly(I:C) treatment ( Figure S6A, middle and right panels) in PKR-depleted cells ( Figure S6D).…”
Section: Nf90/nf110 Promote Circrna Processing By Stabilizing Flankinsupporting
confidence: 90%
“…As expected, the poly(I:C)-stimulation-caused circRNA reduction could be noticeably rescued by overexpression of NF90 for examined circRNAs ( Figure 4I). Furthermore, it has been shown that the NF90/NF110 export depends on PKR activation and phosphorylation upon infection (Harashima et al, 2010;Shiina and Nakayama, 2014). Consistent with these studies, we found that NF90/NF110 were no longer exported to the cytoplasm upon poly(I:C) treatment ( Figure S6A, middle and right panels) in PKR-depleted cells ( Figure S6D).…”
Section: Nf90/nf110 Promote Circrna Processing By Stabilizing Flankinsupporting
confidence: 90%
“…Directly or not, members of the Ilf3 family are involved in all steps of RNA metabolism from transcription to degradation. In addition to the above described functions, mouse Ilf3, but not NF90, was very recently reported to promote the assembly of RNA granules, messenger RNP (mRNP) complexes that regulate mRNA translation and cytosolic localization, whereas NF45 was found to enhance their disassembly in Xenopus cells. Ilf3 association with mRNP complexes requires its specific C‐terminal domain and its promoting assembly activity is regulated by interaction with NF45 as well as by phosphorylation at PKR sites localized in the domain associated with zinc fingers .…”
Section: Resultsmentioning
confidence: 99%
“…More work is required to determine if G3BP1 plays only scaffolding/ recruitment roles, can activate PKR alone, or requires a third factor or several other cofactors to activate PKR. Other PKR-interacting proteins have been described that either activate PKR (PACT, IPS1, and NFAR1/2) or inhibit PKR (MDA7, hDUS2, and p58 IPK ) (46)(47)(48)(49)(50)(51)(52). It would be of interest to investigate whether these proteins also interact with G3BP1-induced SGs and modulate SG assembly.…”
Section: Discussionmentioning
confidence: 99%